Safety culture level among workers in the selected manufacturing plant - Junaidah, Zakaria; Che Rosmani, Che Hassan; Mahar Diana, Hamid; Ezrin Hani, Sukadarin; Zakaria, Razak (IOP Publishing, 2020)
Workers in the manufacturing industry face many safety risks due to the nature of the job. The state of safety and health performance determine by examining the safety climate factors which reflects workers' perception of the psychological aspect in safety culture domain. This study aimed to assess the safety culture level and its contributing factor to the safety culture in a selected chemical manufacturing plant. Survey data was collected from 309 employees in a factory located in Kuantan Pahang. They were randomly selected and represent two groups, namely executive and technician. A standardized climate questionnaire was used and answered by the respondents within 20 to 30 minutes. Sixty-five percent of the total respondents agree that the safety culture level at their workplace is high, and another 35% revealed that it is moderate. Perceived safety climate and personal attitude among two groups employee were compared using an Independent Sample t-test. Results revealed a significant difference between groups (t=7.428, P=0.007) for management commitment, (t=6.133, P=0.014) for safety rules and procedures, (t=15.823, P=0.001) for supportive environment, (t=10.949, P=0.001) and lastly for physical work environment, (t=6.067, P=0.014). A Pearson correlation coefficient was computed to assess the relationship between safety culture factors and demographic information of the respondents. There was a positive correlation between safety rules and procedures and level of education, r = 0.135, p = 0.018, and Involvement and years of working experience, r = 0.165, p = 0.004. Increases in the level of education were found correlated with increases in perceived safety rules and procedures while increases of years of working experience was directly correlated with increases in involvement to safety in the organization.